How a Medication for Opioid Use Disorder Curriculum Translates into Experiences and Internal Medicine Residents' Understanding of Patients with Opioid Use Disorder. Issue 5 (20th October 2022) - Robles, Maria; Mortazavi, Leila; Vannerson, Julie; Matthias, Marianne S.
Abstract: Problem: The number of people with an Opioid Use Disorder (OUD) continues to outpace access to associated medication. Ninety-six percent of states report higher rates of OUD than access to medications, and, despite being the standard of care, only 3% of physicians currently prescribe medication for opioid use disorder (MOUD). Prior studies have shown that decreasing barriers, such as a lack of knowledge about MOUD, increased physicians' willingness to prescribe. However, most internal medicine residency programs do not have a required addiction curriculum. As a result, we created a curriculum and conducted qualitative interviews with residents to better understand experiences with the curriculum. Intervention: In an effort to overcome physician-centered barriers associated with prescribing MOUD, we developed and implemented a week-long curriculum, Addiction Week, for second and third year Internal Medicine Residents at Indiana University School of Medicine in a safety-net clinic. The curriculum included the following: didactics on substance use disorder (SUD), including OUD and alcohol use disorder, and MOUD (mostly buprenorphine), and mostly web-based, peer-reviewed and guideline based readings about addiction, direct observation of addiction counselors, direct discussion with people receiving MOUD, observation of a group therapy session, informal discussion with providers who prescribe MOUD, and, for some residents, observation of a physician prescribing MOUD. After completing the curriculum, the residents participated in an hour long audio-recorded interview to better understand their experiences with the curriculum. Context: This study was completed at a residency program where residents were not previously exposed to outpatient MOUD prescribing. Due to limited availability of faculty treating patients with MOUD, residents spent the majority of their time shadowing a social worker. Impact: Residents described gaining a deeper understanding of OUD by having the opportunity to interact with patients in a stable outpatient setting, which for many led to increased confidence and willingness to prescribe MOUD for people with OUD. Lessons learned: The greater understanding of addiction and willingness to prescribe MOUD described by residents in this study indicate that this type of curriculum may be a promising way to increase MOUD prescribing. Further studies are needed to evaluate whether this intervention can change prescribing behaviors. Supplemental data for this article is available online at https://doi.org/10.1080/10401334.2021.1897597 .